If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2u+4=-8(u+2)
We move all terms to the left:
2u+4-(-8(u+2))=0
We calculate terms in parentheses: -(-8(u+2)), so:We get rid of parentheses
-8(u+2)
We multiply parentheses
-8u-16
Back to the equation:
-(-8u-16)
2u+8u+16+4=0
We add all the numbers together, and all the variables
10u+20=0
We move all terms containing u to the left, all other terms to the right
10u=-20
u=-20/10
u=-2
| 7x+5/2=20 | | c/4+7=10 | | 2p-10=-24 | | 7+7x=x-47 | | 10=2z=2 | | 12=4x-x+3 | | H=6t^2+25t+6 | | (2x-14)+(2x)+(3x+10)=180 | | 7x+6+x=102 | | 9t^2-10t=3t^2-4 | | 2a=9a-9 | | 12(3/4x-2)=8x+11-6x | | 5x+8+7x=80 | | 2y-7=8-3y | | 14=k/3+10 | | -2=0.8a | | 100=6x+4x+10 | | (x-1/x-2)+(x-3/x-4)=10/3 | | 6(-2g-1)=(13+2) | | 2^(2x+3)-57=65(2^x-1) | | x+-90=-187 | | 4(4+x)=3(3+5) | | (x–4.5)2=5.5 | | x—12=105 | | 3x+1=4x—6 | | x+-98=-70 | | 25/yy=5 | | 5x-14=-x+4 | | 90+5x-8+2x-4=180 | | 7=a—70 | | 2(m-6)=8 | | -108=9a |